Meta-analysis of randomised controlled trials testing behavioural interventions to promote household action on climate change - Claudia F. Nisa (Nature Portfolio, 2019)
It is not clear which are the most effective mechanisms to achieve sustainable lifestyle behaviour. Here the authors study the impact of behavioural interventions excluding economic incentives by performing a large-scale meta-analysis and find that these interventions promote sustainable behaviours to a small degree in the short-term with no evidence of sustained positive effects once the intervention is completed.